Inversion Modeling of Dam-Zoning Elasticity Modulus for Heightened Concrete Dam Using ICS-IPSO Algorithm - Wu, Zhongru; Shao, Chenfei; Wu, Bangbin; Gu, Chongshi; Chen, Yijun; Dai, Bo (Mathematical problems in engineering, 2019)
A new approach was developed for the inversion modeling of dam-zoning elasticity modulus for heightened concrete dam, with old and new concrete zones. The proposed inversion modeling procedure takes advantage of the improved cuckoo search (ICS) algorithm and improved particle swarm optimization (IPSO) algorithm to adjust the mechanical parameters, which are used as input. An objective function is constructed based on the horizontal displacement increment by using the finite element method (FEM) and statistical analysis of the prototype monitoring data. One ideal arch dam model and one actual heightened concrete dam were taken as examples. The proposed method was used to implement the optimal selection of the dam-zoning elasticity modulus. The inversion analysis results indicate that the mechanical parameters identification method for heightened concrete gravity dams proposed in this article is accurate and has a fast convergence rate. Consequently, it can be applied as a reliable model to identify the dam-zoning elasticity modulus in practical engineering applications.